Development of Optic-Electric Hybrid Sensors for the Real-Time Intelligent Monitoring of Subway Tunnels. (12th July 2021) - Zhu, Fu-guang; Xu, Dong-sheng; Tan, Rui-shan; Peng, Bin; Huang, He; Liu, Zhuo-wen
Abstract : The settlement and deformation monitoring of subway tunnels had difficult in long-distance and real time measurement. This study proposed an optic-electric hybrid sensor based on infrared laser ranging technology and cable-sensing technology. The working principle, hardware layer, design details, laboratory calibration and field validation were presented and discussed. The optic-electric hybrid sensor implemented the real-time intelligent analysis modulus for the whole system which could analysis the measurement errors and improve the accuracy. The laboratory calibration tests were carried out and the results shown that the hybrid sensors had measurement resolution of 1 mm with the maximum measurement range of 100 m. A remote real-time intelligent monitoring system is established based on the hybrid sensors. The system contains an edge computing module, real-time communication module and warning light signal with three colors. The stability of data acquisition and transmission of the intelligent control monitoring system under long-term conditions was examined. Test results shown that the system was quite stable for the long-term measurement. The whole system was verified in a constructing subway tunnel of Wuhan Metro Line 8, China. According to the field monitoring results, the deformations and the state of health safety of the tunnel was evaluated. The results of this study could provide useful guidance for tunnel deformation monitoring and has great practical value in civil engineering.